PERAN KOMITMEN ORGANISASI DALAM MEMEDIASI PENGARUH KEPEMIMPINAN DAN INTEGRITAS TERHADAP KINERJA PEGAWAI BAPPEDA LITBANG KABUPATEN JEMBRANA - I Nengah Tamba; Muryati; Rahayu Puji Suci (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to analyze the role of organizational commitment in mediating the influence of leadership and integrity on the performance of Bappeda Litbang Jembrana Regency employees. The type of research used in this research is explanatory research with a quantitative approach. The population in this study was all 34 employees. The sample uses nonprobability sampling with a saturated sampling technique (census). The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 4 software. The research results show that leadership plays a role in improving employee performance. Leadership plays a role in increasing organizational commitment. Integrity plays a role in improving employee performance. Integrity plays a role in increasing organizational commitment. Organizational commitment plays a role in improving employee performance. Organizational commitment plays a role in mediating leadership in improving employee performance. Organizational commitment plays a role in mediating integrity in improving employee performance.